Evolution of the radial interstellar medium metallicity gradient in the Milky Way disk since redshift ≈3 - Ratcliffe, Bridget; Khoperskov, S.; Minchev, I.; Lee, N. D.; Buck, Tobias; Marques, L.; Bernaldez, J. P.; Lu, L.; Steinmetz, M. (Astronomy and astrophysics, 2025)
Context: Recent works have identified a way to recover the time evolution of a galaxy’s disk metallicity gradient from the shape of its age–metallicity relation. However, the success of the method is dependent on how the width of the star-forming region evolves over time, which in turn is dependent on a galaxy’s present day bar strength. - Aims: In this paper, we account for the time variation in the width of the star-forming region when deriving the interstellar medium (ISM) metallicity gradient evolution over time (∇[Fe/H](τ)), which provides more realistic birth radii estimates of Milky Way (MW) disk stars. - Methods: Using MW/Andromeda analogs from the TNG50 simulation, we quantified the disk growth of newly born stars as a function of present day bar strength to provide a correction that improves recovery of ∇[Fe/H](τ). - Results: In TNG50, we find that our correction reduces the median absolute error in recovering ∇[Fe/H](τ) by nearly 30%. To confirm its universality, we tested our correction on two galaxies from NIHAO-UHD and found the median absolute error is almost four times smaller even in the presence of observational uncertainties for the barred MW-like galaxy. Applying our correction to APOGEE DR17 red giant MW disk stars suggests the effects of merger events on ∇[Fe/H](τ) are less significant than originally found, and the corresponding estimated birth radii expose epochs when different migration mechanisms dominated. - Conclusions: Our correction to account for the growth of the star-forming region in the disk allows for better recovery of the evolution of the MW disk’s ISM metallicity gradient and, thus, more meaningful stellar birth radii estimates. With our results, we are able to recover the evolution of the ISM gradient, providing estimates for the total stellar disk radial metallicity gradient and key constraints to select MW analogs across redshift.